Konstrukční úlohy Učební text pro studenty učitelství matematiky 2. stupně základní školy - Budínová, Irena (Masaryk University Press, 2020)
Title in English: Construction Tasks: Textbook for Students of Mathematics Teaching at the 2nd Level of Primary School. The publication presents the problems of solving construction problems at primary school. It shows ways of solving basic construction problems and complex construction problems that are given at primary or secondary school. It deals with problems of solving construction problems in Geogebra.